Helicobacter pylori Thioredoxin1 May Play a Highly Pathogenic Role via the IL6/STAT3 Pathway - Yanlei Guo; Shigang Ding (Gastroenterology Research and Practice)
Background. Recent studies have shown that CagA is considered highly pathogenic to helicobacter pylori (HP) in Western populations. However, in East Asia, CagA positive HP can be up to 90%, but not all patients will lead to gastric cancer. Our research group has found that HP thioredoxin1 (Trx1) may be a marker of high pathogenicity. Here, we investigate whether HP Trx1 exerts high pathogenicity and its internal molecular mechanism. Materials and Methods. We constructed the coculture system of high-Trx1 HP and low-Trx1 HP strains with gastric epithelial cell lines separately and detected the influence of HP strains. The cells were stained by AM/PI, and the cell’s mortality was assessed by fluorescence microscope. The cell’s supernatants or precipitates were collected to detect the expression of IL6. In addition, the cell’s precipitates were collected, and the expression of p-STAT3 was detected by western blot. Furthermore, the cell’s supernatants were collected for detecting the expression of 8-OHDG to investigate the extent of DNA damage. Results. The high-Trx1 HP can cause higher mortality of GES-1 cells compared with the low-Trx1 HP group (high-Trx1 HP (4.53±0.56) %, low-Trx1 HP (0.39±0.10) %, P<0.001). The mRNA and protein level of IL-6 in AGS and GES-1 cells were increased during HP infection, and the expression of IL-6 in the High-Trx1 HP group was much higher than the low-Trx1 HP group. Besides, the expression of p-STAT3 was higher in the HP-positive gastric mucosa. And the expression of p-STAT3 in the high-Trx1 HP group was significantly upregulated compared with the low-Trx1 HP group. Furthermore, the expression of 8-OHDG in the high-Trx1 group was much higher than the low-Trx1 group (high-Trx1 HP (5.47±1.73) ng/ml, low-Trx1 HP (2.89±1.72) ng/ml, P<0.05). Conclusion. HP Trx1 may play as a marker of high pathogenicity, and the high-Trx1 HP could mediate the pathogenic process of HP infection via the IL6/STAT3 pathway.